Waffle Ice Cream Based on Jackfruit Seed Flour: Optimization of Ingredient Content Using Response Surface Methodology - Anandhita Putri Cahyaning Sari; Aulia Ulva Zahra; Dea Ramadhani; Savna Gusfany Jhonanda; Yolanda Putri (Interdisciplinary Journal of Advanced Research and Innovation, 2025)
Jackfruit seeds have excellent nutritional quality, so they can help obtain healthy and nutritious food products. In this research, some wheat flour was replaced with jackfruit seed flour as the base ingredient for waffle cone ice cream. The amount of wheat flour added to the dough is the same as the amount of jackfruit seed flour added. Jackfruit seed flour was added after the effectiveness of using response surface methodology in the batter base for waffle ice cream. The waffle ice cream cone was made from 100% wheat flour, was considered a control, and was used to compare the waffle ice cream cone supplemented with jackfruit seed flour. Replacing wheat flour with jackfruit seed flour affects the nutritional content and characteristics of the waffle cone cream for protein content, ice cream permeability density, crunchiness, and overall acceptability. Protein content increased (14.55%) after adding jackfruit seed flour to 80% of the control level. The cone added with 60% jackfruit seed flour resulted in higher overall crunchiness and acceptability scores than other waffle ice cream cones because jackfruit seed flour has a high water/oil absorption capacity, jackfruit seed flour can be used to make other value-added food products as a substitute for wheat flour in whole or part.